Edy Rahmayadi and Musa Rajekshah’s championing factors in Indonesia’s North Sumatra Gubernatorial election in 2018 (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2020)
The gubernatorial election in North Sumatra has been organized in 2008. Two pairs of candidates run in the election, namely Djarot Syaiful Hidayat and Sihar Sitorus (DJOSS), and Edy Rahmayadi and Musa Rajekshah (ERAMAS). Championing the election, several issues have been used to support Edy Rahmayadi and Musa Rajekshah’s victory, such as religious identity politics and the politics of locality, which exploit the identity of so-called ‘son of the soil‘. This study aims to understand how these factors work and determine the victory of ERAMAS.  It focuses on two political means to find out which factors that contribute more significantly in the triumph of ERAMAS candidate. Using descriptive-qualitative methods, this study collects data through a questionnaire with ‘SLOVIN‘ formula to define population and sample selected through random technique. It applies the theories of identity and political participation with a locus of the research in a purposively-selected district in Medan city, Kecamatan Medan Marelan. This research argues that there are three determining factors that contribute to the ERAMAS‘ victory in the Gubernatorial Election of North Sumatra in 2018, which are religious identity politics, politics of locality, and the personal influence of the candidates.